Financial literacy and fintech adoption in Japan - Naoyuki Yoshino; Peter J. Morgan; Trinh Quang Long (Asian Development Bank Institute (ADBI), 2020)
Rapid developments in financial technology (fintech) are expected to contribute to improvements in financial inclusion and well-being. This paper investigates how financial literacy and other factors contributed to the adoption of fintech services in Japan, using data from a survey conducted by the Bank of Japan, including 25,000 individuals aged from 18 to 79. We constructed a financial literacy index from 25 questions relating to financial decision-making skills and financial knowledge. We then analyzed the relationship of this index with the extensive and intensive usage of two types of fintech services-electronic money, and mobile payment apps-and holdings of crypto assets, a type of fintech product. We find that higher financial literacy is positively associated with a higher likelihood of using fintech services but negatively correlated with holding crypto assets. The empirical results also suggest that those with greater financial literacy tend to use fintech services, especially electronic money, more frequently. We also find that the use of fintech services differs for people with different behavioral traits and that greater financial literacy could encourage risk-averse persons to adopt fintech.
Keywords: D14; G11; J26; 330; financial literacy; financial behavior; financial inclusion; household saving; fintech; crypto assets; Japan